(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
An important role in protecting a person from the aggression of the external environment performs immunity. When an antigen - a foreign agent - enters the body, antibodies begin to be produced in the blood. Antibodies or immunoglobulins are specific proteins that are secreted by B-lymphocytes. Their task is to eliminate exactly that “aggressor” that threatens the body at the moment. This means that they act selectively [1,2,3].